Automation and redistribution of work: the impact of social distancing on live TV production. Issue 1 (2nd January 2023) - Okopnyi, Pavel; Guribye, Frode; Caruso, Valentina; Juhlin, Oskar
ABSTRACT: The TV industry has long been under pressure to adapt its workflows to use advanced Internet technologies. It also must face competition from social media, video blogs, and livestreaming platforms, which are enabled by lightweight production tools and new distribution channels. The social-distancing regulations introduced due to the COVID-19 pandemic added to the list of challenging adaptations. One of the remaining bastions of legacy TV production is the live broadcast of sporting events and news. These production practices rely on tight collaboration in small spaces, such as control rooms and outside broadcast vans. This paper focuses on current socio-technical changes, especially those changes and adaptations in collaborative practices and workflows in TV production. Some changes necessary during the pandemic may be imposed, temporary adjustments to the ongoing situation, but some might induce permanent changes in key work practices in TV production. Further, these imposed changes are aligned with already ongoing changes in the industry, which are now being accelerated. We characterize the changes along two main dimensions: redistribution of work and automation.